Interplay between Strain and Defects at the Interfaces of Ultra‐Thin Hf0.5Zr0.5O2‐Based Ferroelectric Capacitors - Greta Segantini; Benoît Manchon; Ingrid Cañero Infante; Matthieu Bugnet; Rabei Barhoumi; Shruti Nirantar; Edwin Mayes; Pedro Rojo Romeo; Nicholas Blanchard; Damien Deleruyelle; Sharath Sriram; Bertrand Vilquin (Advanced Electronic Materials, 2023)
Abstract Hafnium zirconium oxide (HZO) is an ideal candidate for the implementation of ferroelectric memristive devices, due to its compatibility with the complementary metal‐oxide‐semiconductor technology. Ferroelectricity in HZO films is significantly influenced by the properties of electrode/HZO interfaces. Here, the impact of the interfacial microstructure and chemistry on the ferroelectricity of 6 nm‐thick HZO‐based capacitors, realized by sputtering, with titanium nitride or tungsten electrode materials, is investigated. The results highlight a strong correlation between the structural properties of electrode/HZO interfaces and the HZO ferroelectric performance. Interface effects become significant at low HZO thickness, thus the precise control over the quality of electrode/HZO interfaces allows the remarkable improvement of HZO ferroelectric properties. A double remanent polarization of 40 µC cm−2 is achieved. This work is a new step towards high quality ultra‐thin HZO films with enhanced ferroelectricity for the implementation of ferroelectric tunnel junctions for brain‐inspired computing.